Attachment Styles To The Father and Coping Strategies Among Early Adolescents In Banda Aceh City - Fatmawati, Fatmawati; Muhammad Alwi Zainuddin, Nuzsep Almigo Bin (Universitas Islam Indonesia, 2014)
This present study sought to investigate the relationship between attachment styles to the father and coping strategies among early adolescents. The population that has been studied was the seventh grade students ofin one of junior high school in Banda Aceh city that meet the established criteria, specifically at least 12 years old and still have father. The sampling technique applied was universal sampling because the number of eligible population was only 81 students. Total of samples taken consists of 31 males and 50 females. In this study, research instrument used was two different scales, namely Adult Attachment Scale (AAS, Collins & Read, 1990) to measure attachment styles to the father and Self-Report Coping Scale (SRCS, Causey and Dubow, 1992) to measure coping strategies. Statistical test through Regression Analysis was operated to examine the hypothesis. Results showed that close attachment to the father, dependent attachment to the father, and anxiety attachment to the father were positive and strongly correlated with both coping strategies (approach coping strategy and avoidance coping strategy). Hence, it could be concluded that all types ofattachment styles to the father among early adolescents could affect to the choice of either approach coping and avoidance coping.Keywords: attachment styles to the father, coping strategies, early adolescents